Physical characterization of a novel wireless DRX Plus 3543C using both a carbon nano tube (CNT) mobile x-ray system and a traditional x-ray system. (2nd June 2020) - Nitrosi, A; Bertolini, M; Chendi, A; Trojani, V; Canovi, L; Pattacini, P; Iori, M
Abstract: This work aims to characterize the novel DRX Plus 3543C detector in terms of detective quantum efficiency (DQE) using both a mobile x-ray system called Carestream DRX Revolution Nano and a traditional x-ray system (Carestream DRX Evolution). We used the commercial system DRX Revolution Nano, equipped with a new x-ray source based on CNT technology and field emission (FE) as the electron emitter (cathode). An innovative aspect of this device is its intrinsic selection of the focal spot size. We tested the system using three IEC-specified beam qualities (RQA3, 5 and 7) in terms of modulation transfer function (MTF), normalized noise power spectra (NNPS) and DQE as defined in the IEC 62220-1-1:2015. We compared the results obtained using DRX Revolution Nano and DRX Evolution with correlation and with Bland–Altman plots to study their agreement. RQA3 MTF is slightly lower than the RQA5 and 7 curves between 0.5 and 2.5 cycles mm −1 . We measured MTF values of about 0.6 at 1 lp mm −1 and about 0.28 lp mm −1 at 2 lp mm −1 . The NNPS curves show a decreasing trend with the energy regarding the DRX Revolution Nano. On the other hand, the DRX Evolution NNPS curve at RQA3 is greater than the one at RQA5, but the one at RQA5 is less than the one at RQA7. The DQE(0) ranged between about 0.82 (DRX Evolution at RQA3) and 0.54 (DRX Evolution at RQA7). As expected, the squared Pearson's correlation coefficients between the two x-ray tubes were always in an optimal agreement, and Bland–Altman plots confirmed a substantial equivalence between the two physical characterizations of the wireless detector. In conclusion, we can show that the dynamic focal selection of the system equipped with CNT does not play a substantial role in image quality compared to a traditional system in terms of physical characterisation of the detector in our measurement conditions.